Biomechanical difference between single and double scull rowing on water: A case study of a Japanese crew - Yokozawa, T.; Nakamura, M. (Journal of High Performance Sport, 2020)
Although the double sculling technique includes crew coordination, that indicates similar oar motion pattern between rowers, few studies have identified the difference in the oar motion between single and double sculling by the same rowers on water or investigated how to change and control the oar motion in double sculling. This study aimed to identify the control the oar motion and force between rowers during double sculling. In this study, we compared the difference in oar motion and oar force between single and double scull rowing on water using a rowing instrumentation system. Two Japanese female rowers rowed on single scull boats and a double scull boat for every 10 strokes at a pace corresponding to a 2,000 m race. The difference in each parameter at 10 strokes between single and double sculling was tested using a factorial analysis of variance. The recovery time was significantly increased and the stroke rate was significantly decreased in the bow rower during double sculling compared with those during single sculling. Additionally, the time from finish to catch during the recovery phase significantly correlated between the stroke rower and the bow rower in double sculling. The bow rower significantly decreased the oar angular displacement during the driving phase in double sculling to be closer to the value of the stroke rower. On the other hand, the oar force of the bow rower during the first half of the driving phase in double sculling was much smaller than that in single sculling, increasing the bilateral difference and the difference among strokes. It appeared to be reasonable that the bow rower controlled the oar motion adjusting to the stroke rower because the bow rower could watch the motion of the stroke rower.